2022
DOI: 10.3389/fcell.2021.800833
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a Novel Ferroptosis-Related Gene Signature of Atherosclerosis

Abstract: Atheroclerosis refers to a chronic inflammatory disease featured by the accumulation of fibrofatty lesions in the intima of arteries. Cardiovasular events associated with atherosclerosis remain the major causes of mortality worldwide. Recent studies have indicated that ferroptosis, a novel programmed cell death, might participate in the process of atherosclerosis. However, the ferroptosis landscape is still not clear. In this study, 59 genes associated with ferroptosis were ultimately identified in atheroscler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…For example, TLR5-NOX4 signal cascades can stimulate proinflammatory cytokine expression through activation of NF- κ B or regulate smooth muscle cell migration through the TLR5-NOX4-RAC-JNK axis, which leads to the formation of neointimal plaques in atherosclerosis [ 33 ]. In addition, HMOX1 has been identified as a key ferroptosis-related gene in carotid atherosclerosis; however, it has not been thoroughly investigated yet [ 34 , 35 ]. In our study, we will further investigate genes associated with ferroptosis in carotid atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, TLR5-NOX4 signal cascades can stimulate proinflammatory cytokine expression through activation of NF- κ B or regulate smooth muscle cell migration through the TLR5-NOX4-RAC-JNK axis, which leads to the formation of neointimal plaques in atherosclerosis [ 33 ]. In addition, HMOX1 has been identified as a key ferroptosis-related gene in carotid atherosclerosis; however, it has not been thoroughly investigated yet [ 34 , 35 ]. In our study, we will further investigate genes associated with ferroptosis in carotid atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Then, we screened for differentially expressed genes (DEGs) by the R package “limma”, which filters for |log2fold-change (FC)| > 1 and adjusted p < 0.05. Moreover, we analyzed this DEGs using the “clusterProfiler” R package for Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways ( Huang et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, increasing evidence has indicated that ferroptosis driven by iron-dependent lipid peroxidation plays a central role in cardiovascular diseases (CVDs), such as cardiomyopathy, myocardial ischemia/reperfusion injury (MI/RI), heart failure, and atherosclerosis. Inhibition of ferroptosis in cardiomyocytes has been implicated in alleviation of myocardial damage caused at least in part by ferroptosis [ 3 5 ] .…”
Section: Introductionmentioning
confidence: 99%